Pelatihan Tentang Pemahaman Teknik Dasar Olahraga Karate pada Mahasiswa Program Studi Pendidikan Jasmani - Harja, Aditya; Hamid, Faisol; Ma’arif, Ilmul; Wahyu Hidayat, Zakaria (Community Education Engagement Journal, 2024)
Based on the objectives in this service activity has a desire to find out the understanding of students related to basic karate techniques, basic techniques are the initial foundation in karate sports because techniques are the main things that must be mastered by someone in the world of karate sports. So that later students understand and have basic technical skills in the form of movement skills and in this service using lecture, demonstration, practice and question and answer methods. In this activity provides explanations related to basic karate techniques including punches, kicks, parries, and stance positions. In this activity, an evaluation is carried out to be able to summarise related conditions and also suggestions on these activities, while the results of this service increase students' understanding of the material presented positively. The conclusion is that students' understanding of the basic karate technique material has improved well, and has a positive impact on the ability of skills on how to perform basic karate technique movements.